2012
DOI: 10.2298/jsc120518064g
|View full text |Cite
|
Sign up to set email alerts
|

Verifying the modes of cyclic conjugation in tetrabenzo[bc,ef,op,rs]circumanthracene

Abstract: Cyclic conjugation in the "empty" central ring of tetrabenzo- [bc,ef,op,rs]circumanthracene (TBCA) is stronger than in its neighboring "nonempty" rings, contradicting the predictions of Kekulè-structure-based theoretical models. Earlier examples of such anomalous cyclic conjugation were observed in highly strained, non-planar benzenoid systems. Because the molecule of TBCA is perfectly planar and strain-free, its cyclic conjugation pattern could be tested and verified by means of high-level, B3LYP/6- 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Eventually, much effort was devoted to providing a quantitative and theoretically founded re-formulation of the Clar model (see the recent works [18][19][20][21][22][23][24][25][26] and the references cited therein). In earlier studies, 13,14,27,28 examples of benzenoid hydrocarbons were found in which the predictions of Clar theory were violated. However, the benzenoid systems in these examples contained fixed single and double carbon-carbon bonds, and thus, it could be argued that the Clar theory was not strictly applicable to them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, much effort was devoted to providing a quantitative and theoretically founded re-formulation of the Clar model (see the recent works [18][19][20][21][22][23][24][25][26] and the references cited therein). In earlier studies, 13,14,27,28 examples of benzenoid hydrocarbons were found in which the predictions of Clar theory were violated. However, the benzenoid systems in these examples contained fixed single and double carbon-carbon bonds, and thus, it could be argued that the Clar theory was not strictly applicable to them.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Cyclic conjugation in benzenoid hydrocarbons was especially much studied, see the papers [8][9][10][11][12][13][14] and the references cited therein. The "aromatic sextet theory" of Erich Clar 1,3 provides the simplest and most direct way by which an insight into the dominant modes of cyclic conjugation of a benzenoid molecule can be gained.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples documenting disagreements between the actual π-electron structure of benzenoid hydrocarbons, and what is predicted on the basis of the Clar aromatic sextet theory, have been reported in the past [13,14,[24][25][26][27]. The cases studied in this work offer a further indication of such disagreements.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 58%
“…Cyclic conjugation in benzenoid hydrocarbons was especially much studied, see the papers [8][9][10][11][12][13][14] and the references cited therein. Erich Clar's "aromatic sextet theory" [1,3] provides the simplest and most direct way by which one can get an insight into the dominant modes of cyclic conjugation of a benzenoid molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation